Functions and contextual triggers of offensive language on Twitter - Mansour, Deena Mohamed (AUC Knowledge Fountain, 2017)
The use of social media in daily life is dramatically increasing all over the world and microblogging websites, particularly Twitter, have become widespread and excessively used. These web-based mediums of communication host significant social interaction and distinctive user-generated content that are characterized by the use of unique lexical choices and structures. This has led to emergent and diversified research investigating how different the linguistic behavior on these web-based platforms is from other forms of interactions. A controversial linguistic phenomenon on social media is the use of offensive language, which is on the increase and suggests a new domain of linguistic research to answer many questions that have arisen in light of this phenomenon. This phenomenon applies to many languages one of which is Arabic, especially where colloquial Arabic is concerned. This study examines the expressive functions of offensive language on Twitter which were written in Arabic by Egyptians. It also examines the pragmatic categories utilized when this offensive language occurs, as well as the contextual triggers of this type of language. A large purposeful sample of 482 tweets was collected from the Twitter website from different Egyptian tweeps writing in colloquial Arabic. Based on Culpeper's (2010) impoliteness formulae, the collected data was classified into four pragmatic categories: insults, pointed criticism or complaints, negative expressives, and challenging or unpalatable questions. The results show that the offensive language used on Twitter serves expressive functions such as hate, anger, and sarcasm. The results also show that the most common contexts that trigger this offensive use of language are political, economic, personal, and soccer games. The study concludes that the use of offensive language on Twitter has become conventionalized and accepted by this speech community.